A Modelling Framework for the Hydraulic Simulation of a Water Distribution System Under Data Scarcity: Application in the City of Farsala, Greece - Pantelis Sidiropoulos; Achilleas Papadomanolakis; Aikaterini Lyra; Nikitas Mylopoulos; Lampros Vasiliades (Applied Sciences)
Access to safe and reliable water is a fundamental requirement for sustainable urban development. However, water distribution systems (WDSs), particularly in small and aging municipalities, face persistent challenges, including infrastructure degradation, population growth, and limited operational data. This study presents a comprehensive hydraulic modeling framework for the city of Farsala, Central Greece, an area characterized by significant data scarcity and outdated water network records. A novel methodology was developed that combines AutoCAD-based network digitization, GIS data integration, field surveys, and real-time SCADA telemetry to create a high-fidelity and operational hydraulic model using WaterGEMS software. The model was calibrated and validated using observed pressure and flow data, achieving high performance metrics, including a Nash–Sutcliffe efficiency (NSE) of 0.841 and R2 of 0.90. Extended period simulations (EPS) were conducted to evaluate system behavior over a 24 h cycle, revealing critical insights into pressure distribution, peak demand conditions, and leakage hotspots. The results demonstrate that even under constrained data conditions, it is possible to construct a robust and decision-supportive model, offering valuable guidance for future system upgrades, leakage control strategies, and smart infrastructure planning in similar urban environments.